2007
DOI: 10.1073/pnas.0701819104
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod reverses the effects of estrogens on male aggression via genomic and nongenomic pathways

Abstract: Despite recent discoveries of the specific contributions of genes to behavior, the molecular mechanisms mediating contributions of the environment are understudied. We demonstrate that the behavioral effects of estrogens on aggression are completely reversed by a discrete environmental signal, day length. Selective activation of either estrogen receptor ␣ or ␤ decreases aggression in long days and increases aggression in short days. In the bed nucleus of the stria terminalis, one of several nuclei in a neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 52 publications
14
103
1
1
Order By: Relevance
“…A substantial body of work demonstrates that the rapid actions of E2 affect cortically based cognitive function. Object recognition (13,14), reference memory (15), and aggression (26) have been shown to be influenced by acute E2 treatment. Furthermore, long-term potentiation and long-term depression in the forebrain are both enhanced by acute E2 administration (11,12).…”
Section: Combined Rap and Rac Signaling: A Possible Mechanism For Wiringmentioning
confidence: 99%
“…A substantial body of work demonstrates that the rapid actions of E2 affect cortically based cognitive function. Object recognition (13,14), reference memory (15), and aggression (26) have been shown to be influenced by acute E2 treatment. Furthermore, long-term potentiation and long-term depression in the forebrain are both enhanced by acute E2 administration (11,12).…”
Section: Combined Rap and Rac Signaling: A Possible Mechanism For Wiringmentioning
confidence: 99%
“…exposure). Testosterone has its biological effects by binding to specific steroid receptors in target tissues (Simon and Lu, 2005;Trainor et al, 2007). Whether Seoul virus alters the density and distribution of androgen receptors, estrogen receptors, or both remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it appears that photoperiod changes the molecular activity of estrogen receptors. Results from a microarray experiment showed that estrogen-dependent gene expression in the BNST was decreased in short days compared to long days (Trainor et al, 2007a). Furthermore, estradiol injections increased aggression within 15 min in male P. polionotus housed in short days, but had no effect on males housed in long days.…”
Section: Introductionmentioning
confidence: 98%
“…In Syrian hamsters (Mesocricetus auratus) (Garrett and Campbell, 1980;Jasnow et al, 2002;Caldwell and Albers, 2004), Siberian hamsters (Phodopus sungorus) (Jasnow et al, 2000;Demas et al, 2004;Wen et al, 2004), beach mice (Peromyscus polionotus) (Trainor et al, 2007a), and deer mice (Peromyscus maniculatus) (Trainor et al, 2007b), males are more aggressive in a resident-intruder test when tested in short days (8L: 16D) as opposed to long days (16L:8D). This effect has been considered paradoxical, because in each of these species housing in short days causes regression of testes and a corresponding decrease in testosterone (Jasnow et al, 2000(Jasnow et al, , 2002Trainor et al, 2006c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation